Educational Direction in Interpretation - Mushir Ebrahim Awla; Jawad Fake Chome Alhidari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study aims to reveal the concept of educational interpretation for contemporary interpreters, and to clarify what is meant by interpretation and types of interpretations, after providing an appropriate definition of the rules of educational interpretation, and the characteristics of educational interpretation of contemporary interpreters were highlighted, and among those characteristics, the characteristic of faith education that depends on divine control. As a basis in the educational system, the first and most prominent of these characteristics, then followed by the characteristic of realism, which downloads the texts of the Qur’an and its rulings to the reality of the nation to treat issues and problems, and then presents the purposeful characteristic that aims to extract the treasures, secrets and guiding wisdom of the Holy Qur’an, and to clarify the factors affecting the emergence of the educational interpretation.